Problems of knowledge, problems of order: the open science field site - Goldensher, Liora O’Donnell (Frontiers in Sociology, 2023)
Ethnographers can and should not just do or not do open science, but study the push to share data, instruments, and other research materials as an important moment of change and contest in contemporary knowledge-making and knowledge politics. Following ethnographers of science and technology who have demonstrated the analytic opportunities afforded by moments of scientific controversy, we should treat the places where these calls are made, debated, and taken up as important field sites for ethnographic inquiry. Whenever and wherever the sharing of data, instruments, and research is discussed, planned, done, measured, judged, or regulated, there are powerful claims, visions, and action concerning what makes for facticity, legitimacy, and credibility in both research and politics. From these sites, I argue, we can observe changes to disciplinary and popular understandings of epistemic virtue, or what makes for reliable, factual, or adequately transparent knowledge production. Attention to these sites can also yield important perspectives on the ways that visions of proper research conduct are imbricated with visions of governance. I argue that turning ethnographic methods to studying the open science movement can enable us to do timely scholarship about shifting understandings of facticity, knowledge, information, and governance.